Human immunoglobulin C lambda 6 gene encodes the Kern+Oz-lambda chain and C lambda 4 and C lambda 5 are pseudogenes. - Dariavach, P (1987)
Six nonallelic immunoglobulin lambda constant region genes have been previously characterized on a 40-kilobase stretch of DNA. The nucleotide sequences of the three upstream genes of this cluster (C lambda 1, C lambda 2, C lambda 3) have been determined by other workers and shown to encode, respectively, the isotypic Mcg, Kern-Oz-, and Kern-Oz+ constant region of the lambda chains. In this paper, we report the sequence of the three downstream genes of this cluster and show that two of them (C lambda 4 and C lambda 5) are pseudogenes. However, C lambda 6 encodes a Kern+Oz- chain and corresponds to the fourth isotype described among the lambda proteins sequenced so far. A potentially active J lambda (joining) segment, with the canonical heptamer and nonamer sequences for rearrangement, is located 1.5 kilobases upstream of C lambda 6. The amino acid sequence encoded by the C lambda 6 gene is compared with the constant region sequences of various monoclonal Bence Jones lambda proteins. Allotypic and isotypic differences confirm the polymorphism and complexity of the human C lambda locus.